LINGUOCULTURAL CHARACTERISTICS OF THE CONCEPT «GOOD AND EVIL» IN RUSSIAN AND UZBEK PROVERBS - Давлатмуратов Сирож Равшанбекович, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract. The article presents a comparative linguocultural analysis of the verbalization of the concept «Good and Evil» in the paremiological fund of the Russian and Uzbek languages. Based on a corpus of 140 paremiological units (70 Russian and 70 Uzbek) selected by continuous sampling, the universal features and ethnocultural specificity of the representation of moral opposition are examined. It has been established that in the Uzbek linguistic picture of the world the concept of «good» (yaxshilik) is predominantly connected with the idea of communal reward and divine retribution, while the concept of «evil» (yomonlik) is associated with social disgrace and collective condemnation. In Russian paremiology, the moral opposition is realized through pragmatic irony, fatalistic worldview and the idea of inevitable punishment for evil. The results contribute to a deeper understanding of the axiological foundations of the two linguocultures.
Keywords: Keywords: linguoculturology, paremiological fund, concept, good, evil, Russian language, Uzbek language, linguistic picture of the world, axiological opposition, ethnoculture.